2011
DOI: 10.1185/03007995.2011.576237
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective, observational data collection of the treatment of phenylketonuria in the UK, and associated clinical and health outcomes

Abstract: The results support current literature showing that a proportion of subjects with PKU, in particular older subjects, are not fully compliant with their treatment and subsequently have Phe concentrations that depart from national recommendations. However, definitive conclusions may not be drawn due to the retrospective nature of the study and the small number of observed subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Even at a center that managed the transition successfully, not all adult PKU patients were adequately controlled [ 26 ]. Also the failure to find differences between genders is consistent with previous findings [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even at a center that managed the transition successfully, not all adult PKU patients were adequately controlled [ 26 ]. Also the failure to find differences between genders is consistent with previous findings [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Their claims were supported by phenylalanine plasma concentration data: nearly half of them reported a high plasma value over the last 6 months (>600 μmol/L, 48%) or were unable to specify it (31%). This is consistent with the recent findings of the systematic review by Medford (2017) including 29 articles representing 1784 PKU patients of all ages, who found that the main factor associated with worsening of metabolic control was age [ 9 ], as well as a less recent retrospective chart review related to 125 PKU patients that showed that the proportion of adequately controlled subjects diminished considerably after the age of 18 (39% vs 57% between the age of 6 and 17 years) [ 24 ] and general claims in reviews on PKU in the literature [ 25 ]. Increasing age usually involves the transition from a pediatric to an adult setting.…”
Section: Discussionsupporting
confidence: 87%
“…Following age, the next most reproducible factor was child sex, with six studies indicating no association with sex and one study finding that more females had 70% or more of their phe levels within target range than males (MacDonald et al 2011). In this study, the endpoint measure of 70% or more levels within target range might have allowed greater sensitivity with regard to identifying more subtle differences in metabolic control between males and females.…”
Section: Discussionmentioning
confidence: 77%
“…The available evidence indicated that strict adherence to diet therapy is very difficult or impossible in a high percentage of patients (variable, but approximately 35-50%); the recommended metabolic control is not achieved, thus resulting in a significant impact on cognitive functions. More than 50% of these patients have blood Phe values > 600 µmol/L [10][11][12][13][14][15][16].…”
Section: Literature Analysismentioning
confidence: 99%